Toxicity of carbon nanomaterials in Caenorhabditis elegans: Effects of biocorona formation on single and co-exposure testing - Côa, Francine (2023)
This thesis aimed to evaluate the effects of biocorona formation on carbon nanomaterials (i.e., graphene oxide - GO and multiwalled carbon nanotubes - MWCNT) toxicity in the nematode Caenorhabditis elegans model. In the first chapter, a literature review introduced this organism as a valuable model for nanotoxicity research; focusing on carbon nanomaterials toxicity, nanobiointerfaces, and discussing experimental gaps towards harmonization of protocols and best laboratory practices. In the second chapter, bovine serum albumin was exploited as a protein model to investigate the implications of biocorona formation on the toxicity of GO and MWCNT. This study demonstrated that both materials were toxic to nematode survival, growth, reproduction, and fertility, as well as enhanced oxidative stress and permeability of intestinal barrier. They crossed the nematode intestine reaching its secondary organs, but albumin corona hindered the MWCNT translocation, while coated GO was translocated affecting the functionality of crucial organs. As consequence, the effects of GO were 50% attenuated by protein coating, while damages of MWCNT were 100% mitigated. In the third chapter, the combined toxicity of GO and silver nitrate (Ag+) in co-exposure testing was analysed, and the concept of E. coli corona formation was addressed for the first time in the literature. Results suggest that GO increased the lethality of Ag+ 2.1 times, but it was aggravated 4.6 times when GO was coated by E. coli corona. Bare and coated GO were translocated to secondary organs of C. elegans, where they promoted the enhancement of apoptotic corpses in germline and potential injuries to neurons. Therefore, these results suggest that assessing the implications of E. coli corona formation to nanomaterials toxicity must be a priority in the assays with C. elegans. Finally, this thesis provides a fundamental understanding of biocorona role and reinforces the importance of considering its influence on nanomaterials toxicity towards a safer applications of carbon nanomaterials